Effects of centralizing acute stroke services: A prospective cohort study. (17th July 2018) - Hastrup, Sidsel; Johnsen, Soren P.; Terkelsen, Thorkild; Hundborg, Heidi H.; von Weitzel-Mudersbach, Paul; Simonsen, Claus Z.; Hjort, Niels; Møller, Anette T.; Harbo, Thomas; Poulsen, Marika S.; Ruiz de Morales Ayudarte, Noella; Damgaard, Dorte; et al.
Abstract : Objective: To investigate the effects of centralizing the acute stroke services in the Central Denmark Region (CDR). Methods: The CDR (1.3 million inhabitants) centralized acute stroke care from 6 to 2 designated acute stroke units with 7-day outpatient clinics. We performed a prospective "before-and-after" cohort study comparing all strokes from the CDR with strokes in the rest of Denmark to discover underlying general trends, adopting a difference-in-differences approach. The population comprised 22, 141 stroke cases hospitalized from May 2011 to April 2012 and May 2013 to April 2014. Results: Centralization was associated with a significant reduction in length of acute hospital stay from a median of 5 to 2 days with a length-of-stay ratio of 0.53 (95% confidence interval 0.38–0.75, data adjusted) with no corresponding change seen in the rest of Denmark. Similarly, centralization led to a significant increase in strokes with same-day admission (mainly outpatients), whereas this remained unchanged in the rest of Denmark. We observed a significant improvement in quality of care captured in 11 process performance measures in both the CDR and the rest of Denmark. Centralization was associated with a nonsignificant increase in thrombolysis rate. We observed a slight increase in readmissions at day 30, but this was not significantly different from the general trend. Mortality at days 30 and 365 remained unchanged, as in the rest of Denmark. Conclusions: Centralizing acute stroke care in the CDR significantly reduced the length of acute hospital stay without compromising quality. Readmissions and mortality stayed comparable to the rest of Denmark.